Understanding cultural difference management through Charles Taylor's philosophy: Case studies from the food processing industry - Samuel Marleau Ouellet; Joseph Facal; Louis Hébert (Administrative Sciences, 2015)
In this paper, we use the work of the philosopher, Charles Taylor, to investigate the role of culture on internationalization decisions. Using parameters related to key constructs such as positive liberty, social ontology, expressivism, civic republicanism and common spaces, we look at how culture influences the decisions regarding corporate international expansion. This framework was applied in a multi-interview design in four firms from the food processing industry from France and Canada. Results showed an obvious sensitivity to cultural difference and that managerial practices surrounding this issue tended to be intuitive and emergent. These practices were not crystallized in the form of a conscious and deliberate organizational strategy for dealing with cultural difference when planning foreign market entry. Our findings triggered further reflections on managerial implications such as the importance of searching more explicitly for cultural and organizational anchors when reviewing location factors.
Keywords: 350; culture; decision-making; organizational behaviour; internationalization; international business; multinational corporations (MNCs)